2011
DOI: 10.1016/j.exphem.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A human thymic epithelial cell culture system for the promotion of lymphopoiesis from hematopoietic stem cells

Abstract: Objective A human thymic epithelial cell (TEC) line expressing human leukocyte antigen (HLA)-ABC and HLA-DR was engineered to overexpress murine Delta-like 1 (TEC-Dl1) for the purpose of establishing a human culture system that supports T lymphopoiesis from hematopoietic progenitor cells (HPCs). Materials and Methods Cord blood (CB) or bone marrow (BM) HPCs were co-cultured with either the parental TEC line expressing low levels of the Notch ligands, Delta-like 1 and Delta-like 4 or with TEC-Dl1 to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…We first showed that the rabbit adipocyte CM inhibited differentiation of human CD34 + HSC-enriched cells into CD79 + B-lineage cells in co-cultures with OP9 cells (data not shown). We then co-cultured human HSCs and OP9 cells with rabbit adipocyte CM and analyzed the cells for CLPs, pre-proB and proB cells (2830). At day 10, we found that the percentages and absolute numbers of CLPs (CD7 + CD34 + ) were similar in cultures with or without adipocyte CM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We first showed that the rabbit adipocyte CM inhibited differentiation of human CD34 + HSC-enriched cells into CD79 + B-lineage cells in co-cultures with OP9 cells (data not shown). We then co-cultured human HSCs and OP9 cells with rabbit adipocyte CM and analyzed the cells for CLPs, pre-proB and proB cells (2830). At day 10, we found that the percentages and absolute numbers of CLPs (CD7 + CD34 + ) were similar in cultures with or without adipocyte CM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to the de novo generation of TEC progenitors, attempts have been made to reconstitute certain features of thymic environments by artificial means, initially in in vitro studies 72,73 and then using in vivo reconstitutions 74 . Collectively, these studies confirmed the decisive role of the Notch 1 ligand delta-like ligand 4 (DLL4) as a key determinant of T cell lineage induction 75,76 .…”
Section: Artificial Thymopoietic Environmentsmentioning
confidence: 99%
“…Indeed, adult TECs lose their ability to aggregate ex vivo and fail to maintain expression of important molecules, such as those of the Notch signaling pathway, when are not supported by a well‐organized 3D environment. Based on this insight, other researchers were able to successfully establish in vitro bone marrow derived cell lines (OP9‐DL1 or MS5‐Dll4 or MS5‐Dll1) or human thymic stromal cell lines (TEC‐Dl1) overexpressing the Notch ligand delta‐like 1 (Dll1) and Notch ligand delta‐like 4 (Dll4) . Even though these experimental systems were able to partially support thymocyte development in vitro, they could not recapitulate the complexity of the 3D thymic microenvironment and were not meant to create a functional approach for in vivo thymic regeneration.…”
Section: Discussionmentioning
confidence: 99%